2020
DOI: 10.1111/tbed.13714
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and phylogenetic analysis of Porcine circovirus 4 in Henan and Shanxi Provinces of China

Abstract: Porcine circoviruses (PCVs) are very small non-enveloped animal viruses with circular single-stranded DNA genomes of approximately 2 kb, which belong to the genus Circovirus in the family Circoviridae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 18 publications
9
72
1
Order By: Relevance
“…The detection limits of the conventional PCR assays specific for the four species of PCV strains were determined to be 2.8 × 10 2 copies/μl (Figure 3). The results indicated that the sensitivity of our newly developed quadruplex method is similar to previously reported multiplex real‐time PCR assays (Li et al, 2013; Li, et al, 2018; Zhang et al., 2020) but 10 times higher than the previously developed singleplex conventional methods (Tian et al., 2020; Yang et al., 2019; Zhang et al., 2020). To further evaluate the influence on the sensitivity when multiple pathogens were present, four representative PCV1‐4 positive samples were separately and simultaneously detected by the quadruplex real‐time PCR (Table S1).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The detection limits of the conventional PCR assays specific for the four species of PCV strains were determined to be 2.8 × 10 2 copies/μl (Figure 3). The results indicated that the sensitivity of our newly developed quadruplex method is similar to previously reported multiplex real‐time PCR assays (Li et al, 2013; Li, et al, 2018; Zhang et al., 2020) but 10 times higher than the previously developed singleplex conventional methods (Tian et al., 2020; Yang et al., 2019; Zhang et al., 2020). To further evaluate the influence on the sensitivity when multiple pathogens were present, four representative PCV1‐4 positive samples were separately and simultaneously detected by the quadruplex real‐time PCR (Table S1).…”
Section: Resultssupporting
confidence: 85%
“…Conventional and real‐time PCR assays (both singleplex and multiplex) have been developed for the detection and differentiation of PCVs (Li et al, , 2013; Li, et al, 2018; Tian et al., 2020; Yang et al., 2019; Zhang et al., 2020). However, all the developed methods are targeting only one to three species of PCVs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations